Hybrid DARIMA-NARX model for forecasting long-term daily inflow to Dez reservoir using the North Atlantic Oscillation (NAO) and rainfall data. (June 2017) - Banihabib, Mohammad Ebrahim; Ahmadian, Arezoo; Jamali, Farimah Sadat
Highlights: A hybrid model was proposed to evaluate the accuracy of daily flow forecasts. The accuracy is not achieved by using NAO singular or together with rainfall data. The proposed hybrid model decreased the proposed error index from 1.25 to 0.36. Abstract: Proper water resources management cannot be achieved without accessing comprehensive data, suitable resources exploitation programs, and quantified forecasts of water resources. Thus, it is necessary to develop new forecasting models of water resources. Autoregressive integrated moving average (ARIMA) models (classified as time series models) and artificial neural network models have performed well in forecasting linear and non-linear stream flow, respectively. In this paper, a hybrid method was used to evaluate the accuracy of daily flow forecasts through using the capabilities of ARIMA model and nonlinear auto regressive model with exogenous inputs (NARX). Moreover, the efficiency of forecasters such as North Atlantic oscillation (NAO) (as a large scale climate signal) was analyzed for flow forecasts. The forecasting results which compared using proposed error index (IIFFE) to assess mean absolute relative error (MARE), time to peak, and peak flow of forecasted flow. The results showed that forecasting accuracy was enhanced by using the hybrid model. It also displays that using rainfall as a forecaster has the most prominent influence on the increasing forecasting accuracy, while the accuracy is not achieved by using NAO singular or together with rainfall data. Finally, the proposed hybrid model decreased the IIFFE index from 1.25 (achieved by the best ARIMA forecast) to 0.36 and improved the accuracy daily flow forecasting considerably which enhance real time optimal operation of reservoirs.